Sergei Yesenin’s Olfactory and Peculiarities of its Reproduction in Polish Translations (Based on the Example of Selected Works) - Curkan-Dróżka, Ełona (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
Sergei Yesenin is one of the most popular Russian poets in Poland. Interest in his poetry has been undiminished ever since the first translations of Inoniya (Otherland) and Tovarishch into Polish appeared in 1922. Although the literary heritage of Yesenin has been professionally researched by Polish scholars and has attracted a large following of Polish readers for a century, there are gaps in his poetry that need to be filled. The author of this article investigates the role of scents in the poems of Sergei Yesenin, taking into account their changes throughout the creative process, from his juvenile works to his final texts. This approach allows us to present not only the poet’s worldview and his deep connection to the Russian culture, but also to trace the reflection of his individual linguistic worldview in his works. The article also presents a relatively new perspective on the reception of Yesenin’s poetry in Poland, namely the peculiarities and difficulties of translating into Polish the olfactory images used by the poet to convey profound emotions.